Model Asuhan Komprehensif Dalam Mendukung Kelancaran Persalinan Di RSPA Boyolali - Yanti Purnama (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2026)
Smooth labor is an important indicator of successful midwifery care and is influenced by the quality of care provided during childbirth. A comprehensive care model consisting of education, emotional support, pain management, and continuous labor support is expected to facilitate physiological labor and improve maternal outcomes. This study aimed to analyze the relationship between comprehensive care and smooth labor outcomes at RSPA Boyolali. A quantitative correlational study with a cross-sectional approach was conducted involving 30 laboring mothers selected through consecutive sampling. Data were collected using a comprehensive care implementation checklist and a labor outcome assessment instrument covering the duration of the first stage of labor, the second stage of labor, and childbirth complications. Data were analyzed using the Spearman Rho test with a 95% confidence level. The results showed that the mean age of respondents was 25.97±4.72 years, most were multigravida (53.3%), received good comprehensive care (93.3%), and experienced smooth labor (76.7%). Most respondents had a normal first stage of labor (86.7%), a normal second stage of labor (93.3%), and no childbirth complications (93.3%). Spearman Rho analysis revealed a highly significant relationship between comprehensive care and smooth labor outcomes (p<0.001). Comprehensive care has the potential to serve as an effective midwifery care approach to support physiological childbirth and improve the quality of maternity services.